2022
DOI: 10.1107/s2052520622001810
|View full text |Cite
|
Sign up to set email alerts
|

The role of free space in photochemical reactions in crystals at high pressure – the case of 9-methylanthracene

Abstract: The influence of pressure on the course of [4+4] photodimerization in crystals of 9-methylanthracene is presented. The studies were performed at 0.1 and 0.4 GPa. As a result of the reaction at high pressure, crystals of the pure product were obtained, which allowed for monitoring of the reaction until its completion. The initial increase in the unit-cell volume caused by the reaction under ambient conditions was reduced at high pressure due to the decrease in the void volume. Despite the smaller size of the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“… 88 Turowska-Tyrk and coworkers recently showed that photodimerization of single 9MA crystal can be carried to completion without fracture at elevated pressures in a diamond anvil cell. 85 The SSRD structure predicted here (at 0 GPa) is an outstanding match for the experimental X-ray crystal structures reported at 0.1 and 0.4 GPa, with rmsd15 values of only 0.12 Å ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“… 88 Turowska-Tyrk and coworkers recently showed that photodimerization of single 9MA crystal can be carried to completion without fracture at elevated pressures in a diamond anvil cell. 85 The SSRD structure predicted here (at 0 GPa) is an outstanding match for the experimental X-ray crystal structures reported at 0.1 and 0.4 GPa, with rmsd15 values of only 0.12 Å ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 84%
“…Solid-state anthracene [4 + 4] photodimerization reactions only occur when the reactive carbon atoms lie within 4.2 Å and satisfy various orientational constraints. [85][86][87] Moreover, the steric constraints imposed by the crystalline lattice limit molecular reorganization aer the photochemical transformation, thereby constraining the photoproduct crystal structure and inhibiting its relaxation to the lowest-energy SGD packing. Therefore, instead of relying on an energetic stability criterion, we identify the SSRD based on the crystal packing relationships that connect structures between the monomer and photodimer crystal energy landscapes.…”
Section: Crystal Structure Prediction Of Key Intermediates For the Ph...mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand how crystal packing impacts the photomechanical response in these seven crystals, we begin by predicting the unknown solid-state photochemical crystal transformations using the crystalline topochemical approach we recently applied to the solid-state photodimerization of 9-methyl anthracene (9MA), , 9- tert -butyl anthracene ester (9TBAE), ,, and monoclinic 9-anthracene carboxylic acid (9AC). , That study replaced pairs of anthracene molecules from the reactant crystals with their photodimer products positioned to minimize the molecular translation and rotation (by maintaining the center of mass and aligning the axes of inertia). The structures obtained after subsequent DFT optimization of these topochemically generated product crystals closely match the experimental photodimer crystal structures .…”
mentioning
confidence: 99%
“…As noted above, achieving complete photochemical conversion of diarylethene crystals is experimentally difficult, but partially photoreacted crystals of 2a and 2b have been determined as a mixture of open-and closed-form components (Cambridge Structure Database Reference Codes FAWFOY02 and FAWFOY01, respectively). 48,49 To understand how crystal packing impacts the photomechanical response in these seven crystals, we begin by predicting the unknown solid-state photochemical crystal transformations using the crystalline topochemical approach we recently applied 46 to the solid-state photodimerization of 9methyl anthracene (9MA), 54,55 9-tert-butyl anthracene ester (9TBAE), 31,56,57 and monoclinic 9-anthracene carboxylic acid (9AC). 32,58 That study replaced pairs of anthracene molecules from the reactant crystals with their photodimer products positioned to minimize the molecular translation and rotation (by maintaining the center of mass and aligning the axes of inertia).…”
mentioning
confidence: 99%